The accuracy of noninvasive methods in the prediction of clinically relevant outcomes in patients with chronic liver disease. (December 2012) - Fraquelli, Mirella; Pozzi, Roberta
Evaluation of : Chon YE, Jung ES, Park JY et al. The accuracy of noninvasive methods in predicting the development of hepatocellular carcinoma and hepatic decompensation in patients with chronic hepatitis B. J. Clin. Gastroenterol. 46(6), 518–525 (2012). The prognosis of chronic liver diseases, which represent a major public health problem, is mainly linked to the extent and progression of liver fibrosis and the subsequent risk of developing cirrhosis and related complications, mainly hepatocellular carcinoma. The article reviewed here reports on the prognostic role of liver stiffness as measured by transient elastography and other noninvasive methods in the prediction of clinical decompensation and hepatocellular carcinoma in patients with chronic hepatitis B. From the results of the study, liver stiffness measurement, as obtained using transient elastography and other noninvasive tests used to assess liver fibrosis, can accurately predict the development of hepatocellular carcinoma and variceal bleeding in patients with chronic hepatitis B.